2009
DOI: 10.1007/s10533-009-9335-7
|View full text |Cite
|
Sign up to set email alerts
|

34S tracer study of pollutant sulfate behaviour in a lowland peatland

Abstract: Field experiments were carried out in order to assess the practicality and application of 34 SO 4 2-as a tracer of the physical and geochemical fate of aerially derived sulfur in peat. Six enclosures were isolated in a lowland peat with high historical acid sulfate inputs at Thorne Moors, UK, and treated with regular additions of 99.9% pure 34 SO 4 2-for 12 months. The total 34 S sulfate addition resulted in negligible change to the sulfate concentration, but allowed unequivocal change to the isotopic composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The increasing strength of the relationship between sulfate concentrations and the length of the drawdown period is not surprising given that other studies have found that the sulfate that appears during a rewetting event comes from the oxidation of organic sulfur compounds stored in the peat [ Eimers et al , ; Mandernack et al , ; Mörth et al , ]. Isotopic studies of sulfur cycling in peat have found that sulfate added to peatland mesocosms is predominantly incorporated into the organic‐sulfur fraction of the peat matrix through bacterial sulfate reduction and plant uptake [ Bartlett et al , ; Chapman and Davidson , ] and that the sulfate released during rewetting events has a light isotopic signature relative to atmospheric deposition, suggesting reoxidation of sulfur from the “lighter” carbon‐bound sulfur pool [ Mandernack et al , ; Mörth et al , ].…”
Section: Discussionmentioning
confidence: 98%
“…The increasing strength of the relationship between sulfate concentrations and the length of the drawdown period is not surprising given that other studies have found that the sulfate that appears during a rewetting event comes from the oxidation of organic sulfur compounds stored in the peat [ Eimers et al , ; Mandernack et al , ; Mörth et al , ]. Isotopic studies of sulfur cycling in peat have found that sulfate added to peatland mesocosms is predominantly incorporated into the organic‐sulfur fraction of the peat matrix through bacterial sulfate reduction and plant uptake [ Bartlett et al , ; Chapman and Davidson , ] and that the sulfate released during rewetting events has a light isotopic signature relative to atmospheric deposition, suggesting reoxidation of sulfur from the “lighter” carbon‐bound sulfur pool [ Mandernack et al , ; Mörth et al , ].…”
Section: Discussionmentioning
confidence: 98%
“…In contrast to the pore water, in the case of discharge the analysis of the hydrograph and the separation of sources based on event water contributions demonstrated that this inverse relation can be explained by the fact that sulfate and DOC have different hydrological sources, at least in summer: waters of high DOC concentrations and due to reducing conditions low in or devoid of sulfate were released from the wetland waters (wetland pore water, shallow wetland groundwater) during discharge events, while during these events the contribution of deeper groundwater -as the main source of sulfate -decreased. Only during winter months, DOC and sulfate correlated in a positive manner, probably due to changes in hydrological flow paths (e.g., more surface flow components), less activity of reductive processes and also reduced plant uptake (Bartlett et al, 2009). On the other hand there was a strong positive correlation of DOC and iron in pore water, groundwater, and surface water.…”
Section: Pore Water Biogeochemistry and Associated Doc Dynamicsmentioning
confidence: 96%
“…Consistently with previous results (Horsfield, 1997), Wickensen organic matter appears to mainly consist of immature kerogen containing variable amount of organic sulphur moieties. Such sulphur incorporation into organic matter is believed to rapidly occur during bacterial sulphate reduction at the early stages of sediment burial (Sinninghe Damsté; and de Leeuw, 1990;Hebting et al, 2006;Vandenbroucke and Largeau, 2007;Bottrell et al, 2009;Lepot et al, 2009), on time-scales that can be of less than a year (Bartlett et al, 2009). Reactive iron is usually considered to outcompete organic matter for sulphur incorporation, due to faster formation of pyrite (Berner, 1984).…”
Section: Wickensen Samplesmentioning
confidence: 99%